(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Efficient management of restaurant operations and online orders is essential for enhancing customer experience, reducing human error, and improving business productivity. Traditional manual or semi-digital systems often lead to inaccurate billing, delayed order processing, and inventory mismanagement. This study introduces DineCart System, a Python-based application integrating restaurant ordering, billing, and an online shopping cart with an SQLite backend database. Utilizing Object-Oriented Programming (OOP) principles, the system provides a graphical user interface (GUI) for seamless order management, real-time inventory updates, accurate billing, and customer-friendly shopping cart functionality. Functional testing demonstrated that the system correctly handles order creation, transaction processing, inventory adjustments, and receipt generation. By consolidating multiple restaurant management tasks into a single platform, DineCart System streamlines operations, improves accuracy, and enhances the overall efficiency of restaurant service and online ordering processes.